2012
DOI: 10.1021/ol301521n
|View full text |Cite
|
Sign up to set email alerts
|

Transition-State Metal Aryl Bond Stability Determines Regioselectivity in Palladium Acetate Mediated C–H Bond Activation of Heteroarenes

Abstract: Density functional calculations reveal that the stability of developing metal aryl bonds in Pd(II)-acetate C-H activation transition states determines regioselectivity in arene and heteroarene compounds. This kinetic-thermodynamic connection explains the general preference for activation of the strongest C-H bond and provides the possibility for regioselectivity prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 98 publications
5
77
0
Order By: Relevance
“…19,50,51 Indeed, Smith et al have shown that more negatively charged aryl groups stabilize the aryl iridium intermediates. 17 In addition, we also observed a moderate correlation between the Ir−C bond strength and the energy needed to homolytically cleave the C−H bond (R 2 = 0.75; Figure S5), similar to the case for palladium.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,50,51 Indeed, Smith et al have shown that more negatively charged aryl groups stabilize the aryl iridium intermediates. 17 In addition, we also observed a moderate correlation between the Ir−C bond strength and the energy needed to homolytically cleave the C−H bond (R 2 = 0.75; Figure S5), similar to the case for palladium.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…18 In a related study on palladium-catalyzed C(sp 2 )−H activation, Ess et al found a linear correlation between the C−H bond activation energy and the transition state Pd−C bond energy, demonstrating that the stability of the forming Pd−aryl bonds determines regioselectivity for a variety of arene and heteroarene substrates. 19 We recently employed the distortion/interaction model to investigate the origins of reactivity and selectivities in a variety of organic and organometallic reactions. 20−24 The distortion/ interaction analysis has also been called the activation-strain model by Bickelhaupt.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[197] Thus, the kinetic-thermodynamic connection could explain the general preference for activation of the strongest C À H bond in a substrate and allowed prediction of the site selectivity for (hetero)arenes including furan, thiophene, pyridine, pyridine N-oxide, indolizine, five-membered heteroarenes containing two heteroatoms, and polycyclic heteroarenes different from indolizine. [197] In recent years, even transition metal catalysts different from the Pd catalysts have been successfully and conveniently employed for direct arylation of sixmembered heteroarenes containing one heteroatom.…”
Section: P(o)h Was Employed As the Prea C H T U N G T R E N N U N G Lmentioning
confidence: 99%
“…[197] Thus, the kinetic-thermodynamic connection could explain the general preference for activation of the strongest C À H bond in a substrate and allowed prediction of the site selectivity for (hetero)arenes including furan, thiophene, pyridine, pyridine N-oxide, indolizine, five-membered heteroarenes containing two heteroatoms, and polycyclic heteroarenes different from indolizine. [197] In recent years, even transition metal catalysts different from the Pd catalysts have been successfully and conveniently employed for direct arylation of sixmembered heteroarenes containing one heteroatom. In 2009, You and co-workers used the not expensive catalyst system consisting of 20 mol% CuI and 20 mol% 1,10-phenanthroline (Phen) for the high yielding site selective arylation of a wide range of heteroarenes including pyridine N-oxide (287), 2-(paratolyl)pyridine N-oxide (297), quinolone N-oxide (276), furfural (7c), 2-formylthiophene (111e), 2-chlorothioA C H T U N G T R E N N U N G phene (51), some five-membered heteroarenes containing two heteroatoms, and xanthines with aryl bromides.…”
Section: P(o)h Was Employed As the Prea C H T U N G T R E N N U N G Lmentioning
confidence: 99%
“…As a most valuable tool of activating the unreactive carbon-hydrogen bond, transition metal-catalyzed reactions have been extensively and systematically investigated [4,5]. Among transition metals, palladium shows an excellent catalytic performance for appropriate coordinating with all kinds of ligands, such as N-heterocyclic carbenes [6][7][8] and acetate [9][10][11][12] and it has become one of the most effective transition metal catalysts [13][14][15]. Palladium catalysts have been widely used in C-N coupling reactions, like Suzuki-Miyaura reaction [16][17][18], Heck-Mizoroki reaction [19][20][21][22], Stille reaction [23][24][25][26][27] and Sonogashira reaction [28][29][30].…”
Section: Introductionmentioning
confidence: 99%